Quantification of methane sources in the Athabasca Oil Sands Region of Alberta by aircraft mass balance - Baray, Sabour; Darlington, Andrea; Gordon, Mark; Hayden, Katherine L.; Leithead, Amy; Li, Shao-Meng; Liu, Peter S. K.; Mittermeier, Richard L.; Moussa, Samar G.; O'Brien, Jason; Staebler, Ralph; Wolde, Mengistu; et al. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2018)
Aircraft-based measurements of methane (CH4) and other air pollutants in the Athabasca Oil Sands Region (AOSR) were made during a summer intensive field campaign between 13 August and 7 September 2013 in support of the Joint Canada-Alberta Implementation Plan for Oil Sands Monitoring. Chemical signatures were used to identify CH4 sources from tailings ponds (BTEX VOCs), open pit surface mines (NOy and r BC) and elevated plumes from bitumen upgrading facilities (SO2 and NOy). Emission rates of CH4 were determined for the five primary surface mining facilities in the region using two mass-balance methods. Emission rates from source categories within each facility were estimated when plumes from the sources were spatially separable. Tailings ponds accounted for 45% of total CH4 emissions measured from the major surface mining facilities in the region, while emissions from operations in the open pit mines accounted for +/- 50 %. The average open pit surface mining emission rates ranged from 1.2 to 2.8 t of CH4 h(-1) for different facilities in the AOSR. Amongst the 19 tailings ponds, Mildred Lake Settling Basin, the oldest pond in the region, was found to be responsible for the majority of tailings ponds emissions of CH4 (> 70 %). The sum of measured emission rates of CH4 from the five major facilities, 19.2 +/- 1.1 tCH(4) h(-1), was similar to a single mass-balance determination of CH4 from all major sources in the AOSR determined from a single flight downwind of the facilities, 23.7 +/- 3.7 tCH(4) h(-1). The measured hourly CH4 emission rate from all facilities in the AOSR is 48 +/- 8% higher than that extracted for 2013 from the Canadian Greenhouse Gas Reporting Program, a legislated facility-reported emissions inventory, converted to hourly units. The measured emissions correspond to an emissions rate of 0.17 +/- 0.01 TgCH(4) yr(-1) if the emissions are assumed as temporally constant, which is an uncertain assumption. The emission rates reported here are relevant for the summer season. In the future, effort should be devoted to measurements in different seasons to further our understanding of the seasonal parameters impacting fugitive emissions of CH4 and to allow for better estimates of annual emissions and year-to-year variability.